2018
DOI: 10.1111/liv.13923
|View full text |Cite
|
Sign up to set email alerts
|

Early cirrhosis and a preserved bone marrow niche favour regenerative response to growth factors in decompensated cirrhosis

Abstract: Early DC (MELD < 16) patients with mild-moderate ascites and those with a healthy cellular baseline BM respond better to growth factor therapy. Addition of EPO to G-CSF provides better regenerative response than G-CSF monotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 34 publications
(69 reference statements)
1
23
0
Order By: Relevance
“…Strong conclusions cannot be made from the data in the Kedarisetty et al 47 study on survival benefits with GCSF due to the absence of a GCSF-only treatment arm. Similar findings were echoed in the study by Anand et al 55 The authors showed that addition of erythropoietin to GCSF led to better regenerative response than GCSF monotherapy in patients with low MELD score (<16). The need for regenerative cell therapy in patients with low MELD scores and relatively lower mortality rates in the short-and intermediate-term remain debatable in the absence of quality long-term effects with such experimental treatments.…”
Section: Critical Appraisal Of Gcsf In Decompensated Cirrhosissupporting
confidence: 76%
“…Strong conclusions cannot be made from the data in the Kedarisetty et al 47 study on survival benefits with GCSF due to the absence of a GCSF-only treatment arm. Similar findings were echoed in the study by Anand et al 55 The authors showed that addition of erythropoietin to GCSF led to better regenerative response than GCSF monotherapy in patients with low MELD score (<16). The need for regenerative cell therapy in patients with low MELD scores and relatively lower mortality rates in the short-and intermediate-term remain debatable in the absence of quality long-term effects with such experimental treatments.…”
Section: Critical Appraisal Of Gcsf In Decompensated Cirrhosissupporting
confidence: 76%
“…1. One cohort (n=22) represents those cirrhotic patients who received G-CSF therapy in previous study [11] and where stored BM and peripheral blood plasma samples were available (retrospective). The response was considered if there is a reduction of CTP>1 and/or MELD>2 as described [14].…”
Section: Phase-1 Study Participants and Methodsmentioning
confidence: 99%
“…[9,10] A study from our group revealed that those with early cirrhosis and su cient BM reserve could respond to GCSF. [11] Another concern with the progressive stages of cirrhosis is severe cytopenia, including neutropenia.…”
Section: Introductionmentioning
confidence: 99%
“…82 There was an increase in osteoblasts, decrease in neo-vascularization, and an increase in percentage of CD34þ BMSCs in these patients post-G-CSF therapy, suggesting a potential effect of G-CSF in improving bonemarrow response in cirrhosis supporting enhanced hepatic regeneration. 83 Altogether, G-CSF holds the promise of ameliorating gut-derived infection and inflammation, improving bone-marrow and hepatic regeneration process; the major targets for reversal in patients with AH.…”
Section: Effects Of G-csf On Bone Marrowmentioning
confidence: 99%